A cross-sectional study of non-suicidal self-injury in adolescent depression: association with demographic characteristics and physiological indicators - He, Yangliuqing; Wei, Yuhan; Wang, Yiming; Liang, Fenrong; Ma, Tianpei (Frontiers in Psychiatry, 2024)
Introduction Non-suicidal self-injury (NSSI) is a prevalent concern among adolescents with depression, yet its relationship with demographic characteristics and physiological indicators remains underexplored. This study aimed to investigate these relationships among inpatient adolescents aged 13 to 18 at a hospital affiliated with Guizhou Medical University. Methods A cross-sectional study was conducted involving 222 adolescent inpatients diagnosed with depression. Data on NSSI occurrence, demographic variables (gender, only-child status, age), and physiological indicators (ALT, TSH, FT4, PLR, TG, HDLC, LDLC, FT3, NLR, MLR) were collected and analyzed. Statistical analyses, including correlations and group comparisons, were performed to assess the associations between NSSI and these factors. Results The prevalence of NSSI among the participants was 40.5%. Significant correlations were found between NSSI and several demographic and physiological factors. Specifically, NSSI was significantly associated with female gender, non-only-child status, younger age, lower ALT levels, higher TSH levels, lower FT4 levels, and higher PLR values. However, no significant differences were observed in TG, HDLC, LDLC, FT3, NLR, or MLR between the NSSI and non-NSSI groups. Discussion The findings highlight distinct demographic and physiological profiles associated with NSSI among adolescents with depression. The prevalence rate of NSSI underscores its significance as a behavioral manifestation in this population. Further research should explore the underlying mechanisms linking these factors to better inform targeted interventions and treatment strategies for adolescents experiencing NSSI in the context of depression.